EXPERIMENTAL STUDY ON THE TEMPERATURE REDUCTION PATTERNS OF TRANSFORMER OIL PASSING THROUGH A HEAT EXCHANGER - Illiuchenko, P.; Nizhnyk, V. (Municipal economy of cities. Series: «Economy science», 2025)
This study examines the issue of ensuring fire safety of transformers filled with insulating liquid (transformer mineral oils), which are fire-hazardous equipment of transformer substations. Leakage of transformer oil heated to dangerous temperatures (more than 150 ° C - above the flash point) as a result of emergency depressurization of the power transformer housing can lead to the occurrence and spread of a significant fire throughout the substation, since mineral transformer oil is a flammable liquid with an ignition temperature ≤ 300 ° C and a lower heat of combustion ≥ 42 ° MJ / kg. The use of traditional rock backfill (a layer of at least 0.25 m thick of washed gravel or granite rubble or non-porous rubble of another rock with a fraction of 50 mm ± 20 mm) in transformer oil receivers is standard worldwide practice, but it is economically expensive to maintain and may be ineffective for cooling the oil below the flash point during oil leakage during an emergency depressurization of the transformer housing. The research is aimed at developing an effective heat exchange system capable of reducing the temperature of transformer oil below the flash point during its emergency leakage into the oil receiver from the depressurized transformer housing. During the experimental study, the depressurization of the transformer housing and the pouring of heated transformer oil into the oil receiver were simulated - a specially designed heat exchanger with a cooling circuit (corrugated stainless steel tubes) using a phase transition refrigerant (water). The results showed that the temperature of the transformer oil decreased below the flash point while passing through the cooling circuit of the heat exchange system. Based on the results of the research, a mathematical model of the decrease in the temperature of the transformer oil depending on the distance of passage through the cooling circuit of the heat exchange system was developed. The results obtained are the basis for further studies of the dependence of the area of the cooling circuit of the heat exchanger, which ensures the cooling of the transformer oil to a temperature below its flash point in the event of a fire, on the volume of transformer oil in the transformer housing and the diameter of the corrugated tubes of the cooling circuit.